“JIWA” The celebration of memoir / Nur Fatin Umar... [et al.] - Umar, Nur Fatin; Almurid, Dayang Intan Farahanies; Saleh, Nasyirah; Hasim, Nur Syazwani; Ibrahim, Nor Idayu (UiTM Perak Press, 2022)
without any barriers or restrictions. At the end of the making work of art will definitely produce a surplus of art materials that may no longer be used such as glass, paper, wood, fabrics and many more. This artist was inspired to produce works of art using existing materials and used materials, inspired from abstract expressionism artworks. This work is produced from used materials as well as surplus materials including acrylic paint, beads, sequins, embroidered yarn, and cotton twines. The basis of this work is an abstract painting, produced spontaneously by pouring, sprinkling, and spreading. This work is from the KAMI 8 = SI+SA Exhibition in 2020 giving such an inspiring experience to the artist to produce this artwork. Indirectly, this artist gives awareness to the community about the artistic waste.